Inovasi Pelayanan Publik pada Pemerintah Daerah Provinsi Riau - Sri Maulidiah; Rahyunir Rauf; Mala Ricardo Saputra (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This research is motivated by the demands of the community regarding public services and it is necessary to have public service innovations, both those carried out by the government and other community components. This study aims to determine service innovations carried out in Riau Province, especially service innovations in several sub-districts in Riau Province, namely Sungai Mandau District, Siak Regency, Gunung Toar District, Kuantan Singingi Regency and Rambah Hilir District, Rokan Hulu Regency. Furthermore, to determine the inhibiting factors in the implementation of public service innovations in Riau Province. The research method used is a qualitative method with a descriptive approach. The key informants in this study were the sub-districts of Sungai Mandau, the sub-districts of Gunung Toar and the sub-districts of Rambah Hilir. The results show that service innovations have been carried out in several sub-districts such as PATEN on The Road, Zero Compliant, Gerimis Senja (movement to reduce poverty), android information via online about land information in Sungai Mandau District. The Gunung Toar Program BISA, AJAK (Birth Certificate Delivery), SIPATEN GUWA (Integrated Service Information System, Gunung Toar District What Apps), the Village Movement Movement. In Rambah Hiir District, namely: GPP (Public Service Outlets), POSPAY (On-Line Financial Services and Cash Financial Services).